What Explains Differences in the Efficiency of Non-Commercial Bank Financial Intermediaries? Empirical Evidence from Malaysia - Fadzlan Sufian (Asian Academy of Management Journal of Accounting and Finance, 2007)
This paper investigates the performance of Malaysian Non-Commercial Bank Financial Institutions (NCBFIs) during the period of 2000 to 2004. The efficiency estimates of individual NCBFIs are evaluated using the non-parametric Data Envelopment Analysis (DEA) method. The method allows us to distinguish individual NCBFIs technical efficiency (TE) along with its mutually exhaustive components of pure technical efficiency (PTE), and scale efficiency (SE) components. Additionally we have performed a series of parametric and non-parametric tests to examine whether the merchant banks and finance companies were drawn from the same population. The findings suggest that during the period of study, scale inefficiency dominates pure technical inefficiency in the Malaysian NCBFI sector. We found that the merchant banks have exhibited higher technical efficiency relative to its finance companies peers. The results from the parametric and non-parametric tests do not reject the null hypothesis of the merchant banks and finance companies sharing the same production technology, implying that it is appropriate to construct a common frontier.